The Influence of Brand Image, Price, and Fanaticism on the Purchase Decision of J-Hope BTS Concert Tickets in Jakarta - Bunga Artamevia Taru; Nina Fapari Arif (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The K-pop phenomenon is really trendy right now, especially among young folks. It has made many people very enthusiastic about seeing K-pop artists in concert. One such artist is J-Hope from BTS, who is conducting his first solo tour in Jakarta. The purpose of this study is to analyze the influence of brand image, price, and fanaticism in relation to the decision to purchase tickets for J-Hope BTS's concert in Jakarta. The study used quantitative methods. Information was gathered through an online questionnaire using Google Form. The survey consisted of 195 ARMY members who had purchased tickets for the J-Hope BTS concert in Jakarta. The data was analyzed using SPSS 27 and multiple linear regression. The results show that brand image had a significant negative impact on purchasing decisons, as fans were very loyal and fanatical about J-Hope's image from BTS. The price factor also had a significant negative impact on purchasing decisions. On the other hand, fanaticism had a significant positive impact on purchasing decisons, as fans were motivated to purchase tickets as a form of emotional support. These results indicate that K-pop concert marketing strategies must consider fans' feelings and set appropriate prices to encourage more fans to attend.